Iron status and risk factors of iron deficiency among pregnant women in Singapore : a cross-sectional study - Loy, See Ling (2019)
Background: Iron deficiency is the most prevalent nutrient deficiency and the most common cause of anaemia worldwide. Because of the increased iron requirements during pregnancy, iron deficiency can lead to maternal anaemia and reduced newborn iron stores. We examined the proportion and risk factors of iron deficiency among pregnant women in a developed Asian country. Methods: Within a prospective cohort in Singapore, 985 Asian women were assessed for iron status at 26–28 weeks’ gestation, with plasma ferritin and soluble transferrin receptor (sTfR) measurements. Iron status was determined according to plasma ferritin concentrations at ≥30 μg/L (iron sufficiency), 15 to < 30 μg/L (modest iron depletion) and < 15 μg/L (severe iron depletion). Multivariable ordinal logistic regression was used to analyze risk factors for modest and severe iron depletion. Results: The median (25-75th percentile) plasma ferritin concentration was 24.2 (19.9–30.6) μg/L. Overall, 660 (67.0%) and 67 (6.8%) women had modest and severe iron depletion, respectively. Higher plasma sTfR was observed in women with severe iron depletion than among those with iron sufficiency (median 17.6 versus 15.5 nmol/L; p < 0.001). Age < 25 years (odds ratio 2.36; 95% confidence interval 1.15–4.84), Malay (2.05; 1.30–3.24) and Indian (1.98; 1.14–3.44) ethnicities (versus Chinese), university qualification (1.64; 1.13–2.38), multiparity (1.73; 1.23–2.44) and lack of iron-containing supplementation (3.37; 1.25–8.53) were associated with increased odds of modest and severe iron depletion. Conclusions: Nearly three-quarters of Singaporean women were iron deficient in the early third trimester of pregnancy. These results suggest universal screening and supplementation of at-risk pregnancies may be evaluated as a preventive strategy.